Estudio comparativo de las metodologías aplicadas para mejorar el grado de compactación de la panela granulada producida en la parroquia Palo Quemado del cantón Sigchos. - Chávez Pacheco, Shirley Yaily (2023)
The present research project was carried out with the purpose of making a comparative study of the methodologies applied to improve the degree of compaction of the granulated raw sugar cane produced in the Palo Quemado parish of the Sigchos canton; with the supporting link function and responds to the framework agreement with Maquita, the research is part of the Food Production and Good Practices project. For this, the physicochemical analysis of the cane juice samples were carried out, obtaining the following data of the parameters evaluated: for Nanegal 0.0311 % Ca, 1.08 % reducing sugars, 5.52 pH and 0.04 % titratable acidity were obtained meanwhile for the samples of Palo Quemado 0.0258 % of Ca, reducing sugars 2.69 %, pH 5.45 and 0.08 % titratable acidity were recorded. To determine the influence of the charcoal of the rice husk in the cane juice to improve the quality of the granulated raw sugar cane, 3 batches of product were elaborated (without coal, with coal at 5 g and 10 g), By means of the ADVA the statistical significance of the factors was obtained and with the tukey test at 5% it was established that the best result was the raw sugar cane made with 5g of coal, because it has a compaction of 2323 GF with a humidity of 3% which is within the parameters established by the NTE INEN 2332:2002 standard. One sample was exposed to 73% humidity environment and another to 65% humidity with fans, humidity was measured every 1 hour, 2 hours and 3 hours, the best result was raw sugar cane exposed to 65% humidity with fans since in the span of 3 hours it had a humidity of 5,27 %. We conclude that activated coal is an alternative to reduce the compaction that occurs in granulated raw sugar cane, it is also easily accessible and has an accessible price for producers.